2020
DOI: 10.1111/ans.16220
|View full text |Cite
|
Sign up to set email alerts
|

Associations of novel inflammatory markers with long‐term outcomes and recurrence of diverticulitis

Abstract: Background: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have emerged as markers of various outcomes of inflammatory and malignant diseases. The association of those markers with short-term outcomes of acute diverticulitis has been discussed in recent studies. This study aimed at evaluation of the association of NLR and PLR with long-term outcomes in patients presenting with acute diverticulitis. Methods: A retrospective single institute study included patients admitted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
1
13
1
1
Order By: Relevance
“…In most patients with recurrent episodes of acute diverticulitis, biomarkers were elevated both in the first episode and in recurrent attacks. This suggests that NLR might be related to an inflammatory load [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients with recurrent episodes of acute diverticulitis, biomarkers were elevated both in the first episode and in recurrent attacks. This suggests that NLR might be related to an inflammatory load [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, its diagnostic efficacy has not been studied even in our field. Up until now, there are only four studies published in Ireland [ 11 ], Israel [ 12 , 13 ], and South Korea [ 14 ]. The purpose of the study was to determine the usefulness and diagnostic accuracy of NLR in complicated acute diverticulitis (cAD).…”
Section: Introductionmentioning
confidence: 99%
“…Mari et al reported higher mean PLR values in patients who were operated compared to those treated with nonoperative treatment for only complicated diverticulitis [32]. Zager et al suggested that PLR may be related to an in ammatory burden, which may explain the value of PLR in predicting the interval of time between episodes of diverticulitis [33]. Our study demonstrated that PLR was a risk factor for non-operative treatment failure regardless of complicated or uncomplicated diverticulitis.…”
Section: Discussionmentioning
confidence: 47%
“…Mari et al reported higher mean PLR values in patients who were operated compared to those treated with non-operative treatment for only complicated diverticulitis 32 . Zager et al suggested that PLR may be related to an in ammatory burden, which may explain the value of PLR in predicting the interval of time between episodes of diverticulitis 33 .…”
Section: Discussionmentioning
confidence: 99%